Los de arriba, los de abajo, los de aquí: relatos de la sociedad peruana a través del mural del artista Josué Sánchez en la Casa de la Literatura Peruana - Iparraguirre Bernaola, Álvaro (2020)
The text proposes an approach to the artistic production that is being developed in the central sierra of Peru, focusing on one of the many iconic Peruvian artists, such as the Huancaino Josue Sanchez. Through his work, he has looked to recapture the essence of his own culture and history, and also to build a defined style and discourse. Finally, we elaborate a pictographic analysis based on one of his most recognized works, located in the House of Peruvian Literature.